Sistem Informasi Manajemen Riset Unggulan Fakultas Berbasis Web - Tri Mukti Lestari; Begum Fauziyah; Yuyun Yueniwati; Siti Maimunah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Background: The Faculty of Medicine and Health Sciences (FKIK) is one of the faculties at UIN Maulana Malik Ibrahim Malang. FKIK has a vision and mission to develop Hajj health. This is the basis for excellent research for the faculty. The archiving of excellent research on Hajj health and faculty research i carried out independently through each lecturer's e-repository or Google Scholar accounts. This method cannot display the total number of studies that FKIK lecturers have conducted. Then, a web-based faculty research management system was implemented. Objective: To find out the number of publications, especially research related to Hajj health that has been carried out by the entire FKIK academic community that can improve faculty accreditation in particular and improve the quality and quantity of the tridharma of UIN Malang in general. Result: the research management system that has been carried out has resulted in a system that can determine the number of publications and excellent research by the faculty, and makes it easier for the FKIK academic community to participate in research activities. Conclusion: This study concludes that a web-based management system can display the number of superior research in one display (dashboard, making monitoring leading research easier. The advantage of the system is that research submissions and reports can be accessed on one web. Keywords: System, Management, Research